Diskursus 'Iddah Berpersepktif Gender: Membaca Ulang 'Iddah dengan Metode Dalalah al-Nass - Wardah Nuroniyah (Sharia Faculty of State Islamic University of Prof. K.H. Saifuddin Zuhri, Purwokerto, 2018)
Generally â€˜iddah only applies to women (wives), with the ultimate goal of knowing the emptiness of wifeâ€™s womb. But if indeed the sole purpose of â€˜iddah is to know the vacuum of the womb, then it is appropriate that â€˜iddah is only for women, for only women have wombs. In this case, it means that â€˜iddah only relates to sex (gender) and it is natural. However, the function of â€˜iddah is not only to know the cleanliness of a wifeâ€™s womb, but from some other wisdom such as the prevention of infectious diseases, the period of reconciliation, upholding marital problems, and also serving a period of mourning when oneâ€™s partner dies. The wisdom and purpose of â€˜iddah is actually an implementation of the concept of general benefits (al-kulliyat al-khams) namely hifáº“ al-dÄ«n (for religion), hifáº“ al-nafs (for souls), hifáº“ al-â€˜aql (for minds), hifáº“ al-nasl aw al-â€˜ird (for esteems) dan hifáº“ mÄl (for properties/wealth). By using the method of dalÄlah al-dalÄlah, and by taking into account the legal reasoning (â€˜illah al-á¸¥ukm), it is very logically and legally acceptable that the implementation of â€˜iddah is not only for women. The enactment of â€˜iddah for women (wives) and men (husbands) is at least more upholding the human dignity and human rights â€‹â€‹when marriage is concerned. This study uses a philosophical approach, with the aim of trying to find benefit values â€‹â€‹in syariah law from the concept of â€˜iddah, which is based on gender equality.